TEACHERS' VOICES: A CROSS-SUBJECT COMPARATIVE ANALYSIS OF KURIKULUM MERDEKA IMPLEMENTATION PERCEPTIONS - Muthi'ah Qurrota A'yun; Amrullah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Indonesia's educational landscape has undergone significant transformation through Kurikulum Merdeka implementation, yet comparative understanding of educator perspectives across different subjects remains limited. This research investigates comparative perspectives of educators regarding Kurikulum Merdeka implementation across five distinct academic disciplines in Indonesian educational institutions. Employing a qualitative-descriptive methodology, this study examines teacher experiences through comprehensive analysis of peer-reviewed scholarly articles focusing on educator experiences in Mathematics, Indonesian Language, Biology, Islamic Religious Education, and English language instruction. Research findings demonstrate predominantly favorable educator responses (75-80% positive across subjects), particularly appreciating the curriculum's adaptability, learner-focused methodology, and integration of twenty-first-century competencies. However, significant obstacles emerged including extensive preparation requirements, insufficient educational resources, inadequate professional development, and inconsistent educator preparedness levels. These implementation barriers significantly impact comprehensive curriculum adoption and necessitate focused improvements in professional training and resource distribution, with contextualizing approaches to accommodate diverse subject-specific requirements.